Copper technology for all - Gómez R., Alfonso (Base Diseño e Innovación, 2015)
Copptech was created to convey the antimicrobial properties of copper to hundreds of products through cutting-edge technology, thereby having an impact on the daily lives of millions of people in many different markets worldwide.